2017
DOI: 10.1038/srep39528
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in three pri-miRNAs that Target Pepsinogen C with the Risk and Prognosis of Gastric Cancer

Abstract: We aimed to explore the associations of polymorphisms in three microRNAs (miRNAs) (let-7e rs8111742, miR-365b rs121224 and miR-4795 rs1002765) that target PGC with the risk and prognosis of gastric cancer/atrophic gastritis. Sequenom’s MassArray was used to genotype the miRNA polymorphisms in 724 gastric cancer cases, 862 atrophic gastritis cases and 862 controls in a Chinese population. We found that let-7e rs8111742 and miR-4795 rs1002765 were associated with the risk of gastric cancer in the H. pylori-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Disruption of miRNA-mRNA binding may contribute to the development of different types of human diseases. This disruption may result from gene polymorphism at the miRNA target site [34][35][36], or polymorphism in miRNA genes [27,29,30,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of miRNA-mRNA binding may contribute to the development of different types of human diseases. This disruption may result from gene polymorphism at the miRNA target site [34][35][36], or polymorphism in miRNA genes [27,29,30,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, miR-125a suppresses tumour growth, invasion and metastasis by targeting STAT3. In 2016, Xu et al [57] reported that the AA genotype of rs8111742 in miR-125a increased the risk for gastric cancer associated with H. pylori, and this same effect was found by Wu et al [58] in the H. pylori-positive group. SNP rs999885, located at the promoter region of the miR-106b-25 cluster, has been reported to be associated with the risk for hepatocellular carcinoma [59].…”
Section: Discussionmentioning
confidence: 64%
“…PGC can also interact with polymorphisms in miRNAs that target it, including let‐7e, miR‐4795, and miR‐365b. They can bind to the 3′‐UTR region of PGC and inhibit its expression . Our study first reported the SNP interactions of PGC with its neighbor lncRNAs could also affect PGC expression.…”
Section: Discussionmentioning
confidence: 76%
“…They can bind to the 3′-UTR region of PGC and inhibit its expression. 35 Our study first reported the SNP interactions of PGC with its neighbor lncRNAs could also affect PGC expression. PGC protein is a well-known marker for the differentiation of gastric epithelial cells.…”
Section: Discussionmentioning
confidence: 89%